THE USE OF ANIMATION VIDEO TO IMPROVE THE STUDENTS’ ENGLISH SPEAKING SKILL (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this research was to determine the improvement of students speaking skills after being taught through animation video in the seventh grade of SMP Kartika Wirabuana XX-2 Makassar.  The researcher applied the pre-experimental method with one pre-test and post-test and the study lasted for four weeks. The research sample was Class VII of SMP kartika Wirabuana XX-2 Makassar and the number of which was collected using random sampling techniques as many as 20 students in class VII. The techniques used to obtain the data are first, collecting data from the pre-test, second from the post-test and finally drawing conclusions based on the data obtained.The results of the data analysis showed that the average score of students in pronunciation was for pre-test 50.75 and 75.65 for post-test. The average score for vocabulary is 53.75 for pre-test and 78.3 for post-test. This is supported by the significant t-test value is less than 0.05 (0.00 < 0.05).  Therefore, the Alternative hypothesis was accepted and the Null Hypothesis was rejected. And the test scores are significant improvement, it means that once there is treatment by using video animations it is effective and significantly influential in improving students speaking skills because animation video can increase students’ interest in learning, it can facilitate students to understanding the material and strengthening memory because it displays audiovisual-based media. In addition they could learn speaking English through fun activities with their friends. Therefore, they were not bored in the teaching-learning process.